INOVASI MITRA VAST TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DI BAPENDA BALI - Dewa Gede Darma Yoga; I Gusti Ngurah Sanjaya; Ida I Dewa Ayu Manik Sastri (Jurnal Riset Akuntansi Warmadewa, 2025)
The usefulness of Mitra VAST in enhancing Bapenda Bali Province's financial reporting timeliness is examined in this study. A digital vehicle tax payment system called Mitra VAST improves accuracy, efficiency, and transparency. The study, which used a qualitative methodology with in-depth interviews, concludes that Mitra VAST increases administrative efficiency, speeds up reporting, and improves data accuracy. Additionally, it improves financial oversight and transparency. There are still issues, nevertheless, such system optimization and staff adaption. The study emphasizes that in order to increase VAST Partners' efficacy, ongoing training and better technological infrastructure are required. These results offer guidance on how Bapenda and comparable organizations might use digital technology to manage their finances more effectively